Pengkatalogan bahan-bahan Islam: isu dan cabaran = Cataloguing of Islamic materials: challenges and issues - Suja', Balqis (2007)
This is a one-and-a-half hour presentation to enlighten participants on description of Islamic materials, its characteristics and subject coverage, Arabic cataloguing, problems in cataloguing of materials in Arabic script and Islamic materials in non-Arabic language, issues and prospects for solutions at the national level.